2021
DOI: 10.1038/s41598-021-83252-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum 299v probiotic supplementation in men with stable coronary artery disease suppresses systemic inflammation

Abstract: Recent trials demonstrate that systemic anti-inflammatory therapy reduces cardiovascular events in coronary artery disease (CAD) patients. We recently demonstrated Lactobacillus plantarum 299v (Lp299v) supplementation improved vascular endothelial function in men with stable CAD. Whether this favorable effect is in part due to anti-inflammatory action remains unknown. Testing this hypothesis, we exposed plasma obtained before and after Lp299v supplementation from these subjects to a healthy donor’s PBMCs and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…There were 4 and 15 patients in the DAU and non-DAU groups, respectively. A total of 38 samples were obtained from 19 patients before and after oral Lp299v supplementation (Hofeld et al 2021).…”
Section: Microarray Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 4 and 15 patients in the DAU and non-DAU groups, respectively. A total of 38 samples were obtained from 19 patients before and after oral Lp299v supplementation (Hofeld et al 2021).…”
Section: Microarray Datasetsmentioning
confidence: 99%
“…Subsequent studies con rmed that Lp299v possessed a systemic anti-in ammatory effect and reduced the activity of circulatory in ammatory markers, and it was found that the levels of Janus kinase 2 (JAK2), Guanylate-binding protein 1 (GBP1), and TNF superfamily member 10 (TNFSF10) were reduced in blood after oral Lp299v supplementation. ( Hofeld et al 2021) Hence, the present study aimed to identify differentially expressed genes (DEGs) and the core genes, so as to explore the molecular mechanism. In this study, microarray datasets from the Gene Expression Omnibus (GEO) database were downloaded and analyzed to obtain DEGs, and serum levels were measured before and after oral Lp299v in daily alcohol user (DAU) and non-DAU patients with stable CAD (Hofeld et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Suppress inflammatory response. Regulated blood pressure [ 134 ] L. johnsonni 3121 L. rhamnosus 86 Mice 30 males 1 × 10 10 CFU/daily for 84 days Improved lipid metabolism. Suppressed of produce adipocyte.…”
Section: Table A1mentioning
confidence: 99%
“…In a controlled, randomized, double-blinded study, the experimental group who drank beverages containing Lp299v had significantly greater systolic blood pressure, leptin, and fibrinogen than those in the control group, in which a 37% reduction in F2-isoprostaglandin levels and a 42% reduction in IL-6 levels were observed as well (Naruszewicz et al 2002 ). Subsequent studies confirmed that Lp299v possessed a systemic anti-inflammatory effect and reduced the activity of circulatory inflammatory markers, and it was found that the levels of Janus kinase 2, Guanylate-binding protein 1, and TNF superfamily member 10 were reduced in blood after oral Lp299v supplementation (Hofeld et al 2021 ).…”
Section: Introductionmentioning
confidence: 95%